The Ennobling Power of Love in the Medieval German Lyric - Kaplowitt, Stephen J. (UNC Studies in the Germanic Languages and Literatures, 1986)
Every handbook of medieval German literature has stressed the importance of love's ennobling power as a motif in the Minnesang, yet prior to this volume no study had attempted to assess its significance on the basis of its actual occurrence. In this volume Stephen Kaplowitt scrutinizes the entire lyric production of Minnesänger from Der von Kürenberg to Walther von der Vogelweide, identifying and analyzing every example of the motif. He concludes that, although the motif is widespread, its significance has been considerably exaggerated.